Wind Energy Harnessing Options at Buildings - Kostyák, Attila; Szodrai, Ferenc (International Journal of Engineering and Management Sciences, 2016)
Our goal was to develop a wind turbine system which could be applied in urban areas where the wind power has low potential, such as the cities in the “Alföld” region. The proposed system is able to harness more wind power at lower wind velocity than the commonly used ones, by using advantageo us properties of the flow in tunnels.